Severe pediatric asthma therapy: Omalizumab—A systematic review and meta-analysis of efficacy and safety profile - Fenu, Grazia; La Tessa, Andrea; Calogero, Claudia; Lombardi, Enrico (Frontiers in Pediatrics, 2023)
Background Omalizumab is the first biological therapy used to treat moderate-to-severe asthma and certainly the one with the highest number of publications. Methods A systematic review and meta-analysis were performed to examine two critical outcomes of omalizumab therapy, asthma exacerbation rate, the reduction of the use of inhaled corticosteroids (ICS), and the improvement of the lung function as a secondary outcome using the following keywords in the MEDLINE database: “anti-IgE, severe asthma, children, and randomized controlled trial.” We specifically selected papers that included moderate-to-severe asthma patients and collected data on children and adolescents. Results Four RCT studies (total number of patients = 1,239) were included in the analysis. The reported data on exacerbations showed an overall improvement in the exacerbation rate with a decreased use of inhaled steroids and some other minimal clinically important difference (MCID). Conclusions Our systematic review confirms the known findings that omalizumab therapy decreases asthma exacerbation rate and reduces background therapy inhaled steroid dose. Therefore, add-on therapy with omalizumab shows a good efficacy and safety profile, thus proving to be a useful additional therapeutic option. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42023396785.